ANALISIS METODE MIND MAPPING DALAM PROSES PEMBELAJARAN DESAIN GRAFIS - Melini, Ellis; Hananto, Brian Alvin; Suwanto, Kartika Magdalena; Tenardi, Shannon Glenda (Narada : Jurnal Desain dan Seni, 2023)
This study is about the application of the mind mapping method done by a group of design students in the context of graphic design learning. Mind mapping is one of the thinking tools commonly used in the creative thinking process. The goal of this study is to analyze how the participants use this thinking tool and reflect upon its utility as a method applied during the divergent phase in the series of design process. The method used here is a case study, using mixed approaches of qualitative-descriptive and quantitative explanations to measure the qualitative aspects. Results show that the participants can do the mind mapping method, which essentially pertains to its functions, though not rigidly following the formal techniques taught by Buzan. Through comparing the mind maps produced by them with the grades they got for the exploration criteria of their design results, it’s yet to be concluded that the mind map quality can determine the quality of the resulting design.